TEXTUAL OR CONTEXTUAL PARADIGM IN THE INTERPRETATION OF QURAISH SHIHAB; THE VERSES THAT ARE INDICATED BY MISOGYNISTS AS CASE STUDIES - Izzatu Tazkiyah (Jurnal Ilmiah Pesantren, 2019)
Anyone agrees that the Qur’an has the spirit of egalitarianism. Sex differences do not make one of them superior to others. Both have equal rights in education, politics, social and economic. However, the existence of several verses that seem to take sides make the interpreter play a key role in the meaning. Therefore, prior text involvement that binds the mindset of the interpreter is aware or not is a decisive aspect. This study aims to uncover the interpretation of verses that are misogynistic by feminists. The primary source is the interpretation of al-Misbah by Quraish Shihab. By using textual and contextual approaches, at least this research found several points. First, in interpreting the verse which is indicated misogynist classical interpreters tend to be literalist, while modern interpreters are more contextualist. Second, Hawa was created from the same type as the prophet Adam, not from his ribs. Third, taking care of the household is the responsibility of the wife, but this obligation does not make women’s rights - in the public and domestic spaces - isolated.